Síntese e caracterização das ligas Co63Cr28W9-xTax (x = 0, 2, 4, 6 e 9%p) para uso como biomateriais - BATISTA, Beatriz da Silva (2020)
Cobalt (Co) chrome (Cr) based alloys have been used for biomedical applications due to the excellent biocompatibility, corrosion resistance as well as mechanical properties. However, these alloys are not considered bioactive materials, e. i. they don’t form a surface hydroxyapatite (HA) layer when in contact with the biological system which is responsible for the connection between artificial material and living bone. Usually, the alloying elements addition can improve the alloy properties, in this sense it is expected that the addition of a bioactive element such as Ta can improve the bioactivity properties of CoCr alloys. In this study Co63Cr28W9−xTax (x = 0, 2, 4, 6 and 9%p) series of compounds was synthesized aiming to investigate the influence of Ta on the structural, physical, mechanical and bioactive properties of these alloys. Xray Diffraction (XRD), Volumetric Density, Vickers Microhardness (HV), Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM) and Energy Dispersion XRay Spectroscopy (EDS) were are used to characterize the samples. The results indicate that Co63Cr28W9−xTax alloys crystallize ϵCo, αCo and τCoTa phases. Cr and W are distributed in the Co matrix while the Ta addition amount hight than, 4%p, promotes an extra phase (τCoTa) formation. The volumetric density shows a downward trend with the increase of Ta concentration due to the difference between Ta and W density. It was observed an increase in the HV amount in the surface of samples as x increase, indicating that the τCoTa phase contributed to the HV growth. The growth of HA, the samples, after and before thermochemical surface treatment, was evaluated by immersion in Simulated Body Fluid (SBF) for 28 days. XRD and AFM measurements, performed before samples immersion in SBF, indicated the presence of Ta oxides adhesive crystals on the samples surface submitted to thermochemical treatment, which increase the sample surface roughness. XRD and SEM/EDS measurements, performed after sample SBF immersion, indicate the HA growth for the samples with x = 2 to x = 9 submitted to thermochemical treatment, due to the TaOH groups presence. The Ta substitution by W in the CoCrW alloys was efficient to produce alloys within the biomedical standards, with emphasis on the alloy x = 9. In addition, thermochemical treatment was fundamental in alloys bioactivation, through the oxidation of Ta.